On-Going European Space Agency Activities on Measuring the Benefits of Earth Observations to Society: Challenges, Achievements and Next Steps - Tassa, Alessandra; Willekens, Stephanie; Lahcen, Arne; Laurich, Laurent; Mathieu, Charlotte (Frontiers in Environmental Science, 2022)
Understanding the Earth system and its physical and societal processes is crucial for helping humankind develop in a sustainable way, and for designing effective policies across a wide range of applications that include mitigating the effects of climate change, the sustainable management of natural resources, food security and public health. Earth observation (EO) satellites provide regular and accurate observations of the entire planet that can greatly support improvements in such understanding. The European Space Agency (ESA) is committed to supporting international efforts to decipher the processes and phenomena that regulate life on Earth, by building world class EO space missions and making data available to scientists and citizens across the world. How successful is ESA in this endeavour? Given the variable and dynamic nature of EO data use, it is difficult to answer the question through established figures. Yet, it is crucial that ESA be able to discriminate and assess the benefits brought by the use of its EO missions, in order to demonstrate its achievements, to keep improving its systems, to better design and plan future missions, and to promote further uptake. In this article, after recalling its commitments in support of Earth system sciences, ESA’s attempts to conduct valuations of the impact of its own space missions are described. In particular, the challenges encountered in measuring such impacts and the solutions pursued by the Agency to improve its assessment capabilities are detailed, together with the open issues and the current lines of work.